Г.ДӘЎЛЕТОВА ШЫҒАРМАЛАРЫНДА ТЕҢЕЎЛЕРДИҢ ҚОЛЛАНЫЛЫЎЫ - Жолымбетова Ш.A. (FAN va JAMIYAT, 2023)
The article discusses the problems of using simile in G.Davletova wok, and determined their stylistic it is functional reculiarities.